Growth differentiation factor 6 derived from mesenchymal stem/stromal cells reduces age-related functional deterioration in multiple tissues - Hisamatsu, Daisuke; Ohno-Oishi, Michiko; Nakamura, Shiho; Mabuchi, Yo; Naka-Kaneda, Hayato (Aging (Albany, NY.), 2016)
The senescence-associated secretory phenotype (SASP) has attracted attention as a mechanism that connects cellular senescence to tissue dysfunction, and specific SASP factors have been identified as systemic pro-aging factors. However, little is known about the age-dependent changes in the secretory properties of stem cells. Young, but not old, mesenchymal stem/stromal cells (MSCs) are a well-known source of critical regenerative factors, but the identity of these factors remains elusive. In this study, we identified growth differentiation factor 6 (Gdf6; also known as Bmp13 and CDMP-2) as a regenerative factor secreted from young MSCs. The expression of specific secretory factors, including Gdf6, was regulated by the microRNA (miRNA) miR-17, whose expression declined with age. Upregulation of Gdf6 restored the osteogenic capacity of old MSCs in vitro and exerted positive effects in vivo on aging-associated pathologies such as reduced lymphopoiesis, insufficient muscle repair, reduced numbers of neural progenitors in the brain, and chronic inflammation. Our results suggest that manipulation of miRNA could enable control of the SASP, and that regenerative factors derived from certain types of young cells could be used to treat geriatric diseases.